Fontes de informação de antiquários: proposta de um modelo de análise e de categorização - Julia Goncalves da Silveira (2006)
This work focuses the antique dealers problematical. The broad objective of this work was to characterize the information behavior of these professionals, identifying their main information source. A more specific objective was to make up a model of study of information behavior of antique trade professionals. Also, a categorization of theirpreferable information sources that could subsidize planning as well as evaluation and reformulation of specialized information systems. Bibliographical reference was based on specialized literature related to communication, information and theory of knowledge. It was also based on the study of information use and users, memoirs and biographies of antique dealers, as well as information from the database ClassificaçãoBrasileira de Ocupações CBO, from Ministério do Trabalho e Emprego. For a better comprehension of subjects such as memoirs, patrimonies, social nets, sociometry, among others, sciences other than information sciences were searched, as communication, history and sociology. Market research was developed in three different phases. The first one, an exploratory study, was carried out in Belo Horizonte, andconstituted of an interview with an antique store manager, visits and observation to commercial establishments and visits to antique and art fairs and expositions. The second was carried out in the city of Rio de Janeiro, involving five antique stores at Rua do Lavradio, which is part of Rios Cultural Corridor, located in the old citys center. This region of Rio de Janeiro was also chosen for the last phase of the market research. In the last two stages, thirteen antique traders from Rua do Lavradio wereinterviewed, five of them in September 2004 and eight in May 2005. The last eight also answered a sociometry questionnaire, which made possible the sociogram construction. To design of the sociogram was used the software Ucinet, which was developed by Unesco. Complimentary activities of the last two stages, constituted of observations in the work context of antique shops in Rio, visits to antique fairs and expositions located in Rios old city center. For the questions of the interview used in the last stage of the market research, a sense-making approach was applied, combined with the criticalincident technique. The categorization of the information sources of the antique dealers was made according to results of the studies of the sources used by antique traders and writers that were interviewed. Results could prove that initial suppositions related to information behavior and preferable information sources of the antique dealers involved in the research were partially or totally confirmed. This work includes appendix and enclosure.